The range of thermal insulation in the tissues of the new-born baby - Hey, E. N. (1970)
1. Rectal temperature and skin temperatures were measured in twenty-eight naked babies weighing 1·1-4·5 kg, lying supine in environments of 25-31 °C when air speed was 4-7 cm/sec. The ratio of external insulation to internal or tissue insulation for the whole body averaged 2·7 but varied inversely with body weight; the ratio was higher than this on the trunk, and five times lower than this on the hand and foot. The mean ratio rose threefold when environmental temperature was increased to 34-35° C. 2. Direct measurements of heat flow from the back of a hand placed in a water jacket maintained at 32° C were made in thirty-three babies. Heat loss averaged 3 kcal/m(2).hr.° C at low environmental temperature, but the loss was often rather less than this in the first 24 hr of life. Heat loss from the hand increased three- to fourfold, during exposure to an environment of 35° C. 3. When babies more than 48 hr old were exposed to an environment of 34-35° C, heat loss from the hand only increased when rectal temperature reached between 36·6 and 37·3° C; a slightly higher rectal temperature was usually reached before heat loss rose in babies less than 24 hr old. 4. Similar methods were used to study specific tissue insulation in three babies with congenital defects of the brain who lacked evidence of temperature control. No changes in insulation were detected in these three babies following changes in environmental temperature. 5. It is concluded that the range and pattern of control that can be exerted over the specific thermal insulation of the tissues is essentially the same in babies 2-20 days old as it is in adult life.